The compensation system in the security guarding service - David, Sothie Naysadorai (2011)
The question of compensation for the average Malaysian security guard has been widely debated industrial captains in the security industry field, with MTUC leading the way there is a hope for the people who guard our front door. While this is being investigated in this paper we have to take cognizance of the fact that there exists a wide gap of disparity in the attention, care and industrial recognition of them. This paper does not look into the fact that the remuneration system of the security guards, it also looks into the trends as to where the industry is moving into. In this age of knowledge workers, one may take a broad view of the industry, thus the varying social views, industry is given a microscope look in this paper. The outcome of this paper is not only investigate, objective and relevant, but also may render some assistance to those who would pursue this industry with passionate commitment and unfaltering faith.